Investigation of endoscopic findings in nine cases of Helicobacter suis‐infected gastritis complicated by gastric mucosa‐associated lymphoid tissue lymphoma. Issue 3 (1st April 2022) - Kadota, Hiroki; Yuge, Ryo; Miyamoto, Ryo; Otani, Rina; Takigawa, Hidehiko; Hayashi, Ryohei; Urabe, Yuji; Oka, Shiro; Sentani, Kazuhiro; Oue, Naohide; Kitadai, Yasuhiko; Tanaka, Shinji
Abstract: Background: We have previously reported that eradication therapy was more effective against Helicobacter pylori (Hp) ‐negative gastric mucosa‐associated lymphoid tissue (MALT) lymphoma in non‐ Helicobacter pylori Helicobacter (NHPH)‐positive cases than in NHPH‐negative cases and that the infection status of NHPH could be a predictive marker for the efficacy of eradication therapy for H. pylori negative gastric MALT lymphoma. However, a diagnostic test for NHPH infection has not yet been clinically established. In this study, we investigated the endoscopic findings in cases of H .  suis ‐infected gastritis associated with gastric MALT lymphoma reported at our institution. Materials and Methods: Participants were selected from cases of gastric MALT lymphoma who underwent esophagogastroduodenoscopy at Hiroshima University Hospital, who were negative for the API2 ‐ MALT1  gene, and who received eradication therapy as a first‐line treatment. We examined the endoscopic findings in nine cases from this group in which H .  suis infection was confirmed by polymerase chain reaction. Results: Endoscopic findings, such as cracked mucosa, spotty redness, nodular gastritis‐like appearance, and white marbled appearance, which have been reported as characteristics of NHPH gastritis, were observed in multiple cases. The most common endoscopic findings in this study were cracked mucosa (7/9 cases), followed by spotty redness (6/9 cases), nodular gastritis‐like appearance (5/9 cases), and white marbled appearance (2/9 cases). Conclusions: Our study may serve as a reference for re‐evaluation of the diagnostic criteria for H .  suis infection and indications for eradication therapy, particularly for cases of H. pylori negative gastric MALT lymphoma, where endoscopic findings such as those seen in this study were observed in the background mucosa.